ANALISIS STRUKTURAL CERPEN "DAULATU AL-‘ASHAFIIR” KARYA TAUFIK AL-HAKIM - Endang Mustika Sari; Emy Lailatus Sa'idah (Al-Lahjah, 2020)
Literary work is a work of fiction that contains the imagination of an author in describing various problems and events in human life. Literary work is a complex structure. This complex structure consists of various elements. The parts (elements) of the literary work have meaning in relation to the others and the whole. Literary works have several types (genres). Among these types of literary works are short stories (short stories). Short stories in Arabic literature are known as qiṣṣah qaṣīrah. Short stories can also be divided into three groups, namely ordinary short stories, long short stories and short short stories. One of the Arabic short stories is "Daulatu al-‘Ashafiir" by Taufik al-Hakim in the anthology of "Arini Allah". This study aims to analyze short stories from structural aspects. This will be known through the theme; story facts consisting of plot, characters, characterizations and settings; the means of the story consisting of conflict, climax, point of view and language style; and the relationship between elements in this short story. The research method used is descriptive-qualitative method with a structural approach. Based on the results of data analysis, it can be concluded that the theme of the short story is a learning given by a father to a baby bird about his life experience facing lazy and greedy human nature. This short story using a straight or progressive groove. The main character in this short story is a bird father and his child. The additional characters in this short story are humans. The background in this short story consists of three kinds, the setting of the place, namely the time setting, and the socio-cultural background. This short story is told from the point of view of an unlimited third person type. Each has intrinsic elements interrelated with one another so that together produce meaning intact.